Percutaneous liver biopsy – indications, contraindications and possible complications - Gutkowski, Krzysztof (Przewodnik Lekarza/Guide for GPs, 2008)
Conventional, percutaneous liver biopsy is the gold standard in the diagnosis and staging of many hepatic disorders. The histopathological analysis of the obtained liver tissue specimen provides a wide variety of important data about internal structure, the nature of the damage and its grading, and is unusually helpful in monitoring administrative therapy efficiency. According to the patient’s clinical condition and diagnostic issue to be resolved, several methods of procuring liver tissue can be used. These methods include: percutaneous liver biopsy, fine needle aspiration liver biopsy, transjugular liver biopsy via right internal jugular vein, laparoscopic liver biopsy and wedge liver biopsy during laparotomy. The most commonly performed method in modern medical practice is percutaneous liver biopsy. This method is generally very safe in experienced hands and the value of obtained results significantly surpasses the risk of potential complications. The aim of this article is to present the issue of percutaneous liver biopsy with special consideration of indications, contraindications and possible complications.